Yield of conilon coffee using the programmed pruning cycle and different cultivation densities - Verdin Filho, Abraão Carlos; Tomaz, Marcelo Antonio; Ferrão, Romário Gava; Ferrão, Maria Amélia Gava; Fonseca, Aymbiré Francisco Almeida da; Rodrigues, Wagner Nunes (Coffee Science - ISSN 1984-3909, 2014)
Determining the correct population of plants and number of orthotropic stems to be kept per area, along with optimal pruning management, is very important for crops of Coffea canephora. The aim of this work was to improve conilon coffee cropping management, evaluating the influence of the programmed pruning cycle with different combinations of spacing and numbers of orthotropic stems per plant on crop yield. Two experiments were carried out: one with smaller spacing and lower numbers of stems per plant, and another with larger spacing and higher numbers of stems per plant. Both assays followed a triple factorial scheme 2 x 3 x 4 (2 spacing x 3 numbers of stems per plant x 4 harvests) in a random block statistical design, using four replications and 11 plants pen plot. The results show that a reduction in spacing associated with an increase in number of stems per plant has a positive effect on the conilon coffee yield.